2019
DOI: 10.1016/j.medengphy.2019.03.014
|View full text |Cite|
|
Sign up to set email alerts
|

Foot trajectories and loading rates in a transfemoral amputee for six different commercial prosthetic knees: An indication of adaptability

Abstract: This is a repository copy of Foot trajectories and loading rates in a transfemoral amputee for six different commercial prosthetic knees: An indication of adaptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…A study that was done in able-bodied individuals also found correlations between higher GRFs and stress fractures [22]. Although there may be a variety of factors such as prosthetic components [54,55], physical conditions [56,57], and other gait parameters such as velocity and motor control [54,58] that can affect GRFs and GRIs on individuals with amputation, our results indicate that increasing step frequency is a viable strategy to reduce GRFs or GRIs. Therefore, reduction of GRFs or GRIs by increasing step frequency may have implications to reduce potential injury risk during running in individuals with amputation.…”
Section: Discussionsupporting
confidence: 55%
“…A study that was done in able-bodied individuals also found correlations between higher GRFs and stress fractures [22]. Although there may be a variety of factors such as prosthetic components [54,55], physical conditions [56,57], and other gait parameters such as velocity and motor control [54,58] that can affect GRFs and GRIs on individuals with amputation, our results indicate that increasing step frequency is a viable strategy to reduce GRFs or GRIs. Therefore, reduction of GRFs or GRIs by increasing step frequency may have implications to reduce potential injury risk during running in individuals with amputation.…”
Section: Discussionsupporting
confidence: 55%
“…Adjustments, such as increasing the threshold or the minimum required steps, may be necessary. Conversely, amputees often exhibit gait asymmetry, resulting in smaller ground reaction forces from their prosthetic limb, as observed by A. Abouhossein et al [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The kinematics are measured by using motion capture systems that acquire data on ranges of motion [44,46,49,50,[52][53][54][56][57][58][59][61][62][63][64][65][66]69,70,75,77,[79][80][81][82][85][86][87][88][89][90][91][92][93][94]96,99,102,104,[106][107][108]111,112,[114][115][116][117][118][119][120]…”
Section: Functionmentioning
confidence: 99%